INFLUENCE OF NI++ AND FE++ ON THE ANAEROBIC BIODEGRADATION OF ORGANIC WASTE SUSPENSION - Sriwuryandari, Lies; Sembiring, T. (Teknologi Indonesia, 2009)
Study of the effect of trace elements of Ni and Fe and acidity on the biodegradation of organic material in anaerobic condition was executed in serum vials. Effect of ferrous, nickel, its combination and acidity were determined by the measurement of volatile fatty acids, methane, hydrogen, and organic materials concentration during the experiment. The influence of nickel and ferrous on the biodegradation of organic materials shows that ferrous was more favorable although nickel is an essential element for methanogens. Iron stimulated gas production more quickly than nickel did in anaerobic digestion even for organic material elimination was better in the presence of iron rather than nickel. Effect of acidity on the biodegradation shown that pH should be above 6.5 to have an optimum degradation of organic substances.